AIST Superannuation Governance: Paper Examining International and Australian Governance Trends - Volpato , Karen; Scheerlinck , Eva (Journal of Law and Governance, 2015)
The Australian Government is seeking to introduce major changes to the governance of superannuation funds. Industry superannuation funds in Australia often have an executive board of directors in which the composition of the boards is based on equal representation of the number of directors elected by the Members and by the employer organisation. One of the major tenets of governance is the appointment of independent directors. The Government has issued a discussion paper in which it was suggested that this should be adopted by the superannuation funds. This paper argues on behalf of the Australian Institute of Superannuation Trustees (AIST) why this change is not necessary and how under the current model the funds are compliant with the governance standards of the Australian Prudential Regulation Authority (APRA) and the Australian Securities Exchange (ASX).